Brain delivery of camptothecin by means of solid lipid nanoparticles: formulation design, in vitro and in vivo studies - Martins, Susana; Reimold, Isolde; Fricker, Gert (International journal of pharmaceutics, 2012)
For the purpose of brain delivery upon intravenous injection, formulations of camptothecin-loaded solid lipid nanoparticles (SLN), prepared by hot high pressure homogenisation, were designed. Incorporation of camptothecin in the hydrophobic and acidic environment of SLN matrix was chosen to stabilise the lactone ring, which is essential for its antitumour activity, and for avoiding premature loss of drug on the way to target camptothecin to the brain. A multivariate approach was used to assess the influence of the qualitative and quantitative composition on the physicochemical properties of camptothecin-loaded SLN in comparison to plain SLN. Mean particle sizes of ≤200nm, homogenous size distributions and high encapsulation efficiencies (>90%) were achieved for the most suitable formulations. In vitro release studies in plasma, showed a prolonged release profile of camptothecin from SLN, confirming the physical stability of the particles under physiological pH. A higher affinity of the SLN to the porcine brain capillary endothelial cells (BCEC) was shown in comparison to macrophages. MTT studies in BCEC revealed a moderate decrease in the cell viability of camptothecin, when incorporated in SLN compared to free camptothecin in solution. In vivo studies in rats showed that fluorescently labelled SLN were detected in the brain after i.v. administration. This study indicates that the camptothecin-loaded SLN are a promising drug brain delivery system worth to explore further for brain tumour therapy.
Gesehen am 09.05.2018